Brain dysconnectivity relates to disability and cognitive impairment in multiple sclerosis. Issue 3 (26th November 2020) - Sjøgård, Martin; Wens, Vincent; Van Schependom, Jeroen; Costers, Lars; D'hooghe, Marie; D'haeseleer, Miguel; Woolrich, Mark; Goldman, Serge; Nagels, Guy; De Tiège, Xavier
Abstract: The pathophysiology of cognitive dysfunction in multiple sclerosis (MS) is still unclear. This magnetoencephalography (MEG) study investigates the impact of MS on brain resting‐state functional connectivity (rsFC) and its relationship to disability and cognitive impairment. We investigated rsFC based on power envelope correlation within and between different frequency bands, in a large cohort of participants consisting of 99 MS patients and 47 healthy subjects. Correlations were investigated between rsFC and outcomes on disability, disease duration and 7 neuropsychological scores within each group, while stringently correcting for multiple comparisons and possible confounding factors. Specific dysconnections correlating with MS‐induced physical disability and disease duration were found within the sensorimotor and language networks, respectively. Global network‐level reductions in within‐ and cross‐network rsFC were observed in the default‐mode network. Healthy subjects and patients significantly differed in their scores on cognitive fatigue and verbal fluency. Healthy subjects and patients showed different correlation patterns between rsFC and cognitive fatigue or verbal fluency, both of which involved a shift in patients from the posterior default‐mode network to the language network. Introducing electrophysiological rsFC in a regression model of verbal fluency and cognitive fatigue in MS patients significantly increased the explained variance compared to a regression limited to structural MRI markers (relative thalamic volume and lesion load). This MEG study demonstrates that MS induces distinct changes in the resting‐state functional brain architecture that relate to disability, disease duration and specific cognitive functioning alterations. It highlights the potential value of electrophysiological intrinsic rsFC for monitoring the cognitive impairment in patients with MS. Abstract : This MEG study demonstrates that MS induces distinct changes in the resting‐state functional brain architecture that relate specifically to disability, disease duration and specific cognitive functioning alterations. It highlights the potential value of electrophysiological intrinsic rsFC for monitoring the cognitive impairment in patients with MS.